2001
DOI: 10.1051/vetres:2001133
|View full text |Cite
|
Sign up to set email alerts
|

Herd factors associated with the seroprevalences of Actinobacillus pleuropneumoniae serovars 2, 3 and 9 in slaughter pigs from farrow-to-finish pig herds

Abstract: -This cross-sectional epidemiologic study was conducted in 150 randomly selected farrowto-finish pig herds to investigate descriptive epidemiological characteristics of infections with three different serovars of Actinobacillus pleuropneumoniae, and to identify risk factors for the within-herd seroprevalences of these serovars. Different farm characteristics (n = 28) were examined as potential risk factors for the percentage of pigs with antibodies against serovars 2, 3 and 9. The presence of antibodies was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 20 publications
(20 reference statements)
2
27
0
1
Order By: Relevance
“…In a previous study, we showed that the proportion of A. pleuropneumoniae infected pigs at time of weaning was approximately 30% and clustered at litter level (Tobias et al, 2014). For piglets free from A. pleuropneumoniae at the time of weaning, it is not clear when they become infected, but at time of slaughter the prevalence may nearly be 100% (Maes et al, 2001;Chiers et al, 2002;Tobias et al, 2012).…”
Section: Introductionmentioning
confidence: 90%
“…In a previous study, we showed that the proportion of A. pleuropneumoniae infected pigs at time of weaning was approximately 30% and clustered at litter level (Tobias et al, 2014). For piglets free from A. pleuropneumoniae at the time of weaning, it is not clear when they become infected, but at time of slaughter the prevalence may nearly be 100% (Maes et al, 2001;Chiers et al, 2002;Tobias et al, 2012).…”
Section: Introductionmentioning
confidence: 90%
“…The presence of A pleuropneumoniae in both herds was further confirmed by the detection by serology of serotypes 1, 9 or 11 in both herds, as well as serotype 2 in herd B. These serotypes are commonly isolated in Belgium, and have been associated with pleurisy lesions at slaughter (Maes and others 2001). …”
Section: Discussionmentioning
confidence: 80%
“…In our study, the high seroprevalence of M. hyopneumoniae and A. pleuropneumoniae could be associated with the introduction of breeding animals (including local domestic pigs or freeranging pigs) in wild boar farms. Transmission of M. hyopneumoniae by carrier pigs is considered to be the main source of infection under field conditions as infected pigs may harbour the microbe in the respiratory tract for a long period (Maes et al 2001;Pieters et al 2009). …”
Section: Discussionmentioning
confidence: 99%